EKSPERIMENTASI MODEL MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL), GROUP INVESTIGATION (GI) DAN THINK PAIR SHARE (TPS) PADA MATERI BANGUN RUANG SISI DATAR DITINJAU DARI KREATIVITAS SISWA - Hidayati, Dwi; Mardiyana, Mardiyana; Sari Saputro, Dewi Retno (Jurnal Pembelajaran Matematika, 2015)
Abstract. The aim of the research was to determine the effect of learning models on learning achievement viewed from student learning creativity. The learning models compared were problem based learning, group investigation and think pair share. This research used the quasi-experimental research method. The population of the research was all of the students in Grade VIII of Junior Secondary Schools of Banyumas Regency. The samples of the research were taken by using the stratified cluster random sampling technique. The sample of research consisted of 295 students. Techniques of collecting data used were documentation, test, and questionnaire. Balance test used one way ANOVA test. From the research, it can be concluded as follows. (1) Learning model of PBL gave better mathematics learning achievement than model of GI and TPS, model of GI gave better mathematics learning achievement than model of TPS, (2) students who have high creativity gave better mathematics learning achievement than students who have medium and low creativity, students who have medium creativity gave better mathematics learning achievement than students who have low creativity, (3) in the students with high and low creativity, the GI learning model gave the same learning achievement in mathematics with the PBL and TPS learning model, the PBL learning model gave better learning achievement in mathematics the TPS learning model. The PBL, GI and TPS learning model gave the same learning achievement in mathematics, (4) in the PBL and GI learning model, the learning achievement in mathematics of the students with high creativity were better than the students with medium and low creativity, the students with medium and low creativity gave same the learning achievement in mathematics. In the TPS learning model, the students with high and medium creativity gave the same learning achievement in mathematics, the learning achievement in mathematics of the students with the high and medium creativity were better than the students the low creativity.Keywords: Problem Based Learning, Group Investigation, Think Pair Share, Student Learning Creativity